Contemporary challenges of Slovene immigrant writers - Kocjančič, Cvetka (Two Homelands, 2001)
An emigrant writer has an ideal opportunity to contribute positively to the culture of one’s homeland in a manner that one shares the abroad-acquired knowledge and wisdom with one’s fellow countrymen. And vice versa: one can enrich a new environment with values from one’s original culture. The author strives for respect of Slovene cultural values and for strengthening of self-confidence. She point out the danger of automatic assuming of foreign “erudition”. The author refers to the ethic imperative in culture and in art. The creators should act out of love towards people in their ethnic circle, from love towards the old and the new homeland, and from love towards all people of the world.